2018
DOI: 10.1016/j.tibs.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Amazing Diversity in Biochemical Roles of Fe(II)/2-Oxoglutarate Oxygenases

Abstract: Since their discovery in the 1960s, the family of Fe(II)/2-oxoglutarate-dependent oxygenases has undergone a tremendous expansion to include enzymes catalyzing a vast diversity of biologically important reactions. Recent examples highlight roles in controlling chromatin modification, transcription, mRNA demethylation, and mRNA splicing. Others generate modifications in tRNA, translation factors, ribosomes, and other proteins. Thus, oxygenases affect all components of molecular biology's central dogma, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
173
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(186 citation statements)
references
References 112 publications
3
173
0
1
Order By: Relevance
“…The application of a semi-empirical model of heterogeneous thin layer electrochemistry showed that both models can yield comparable NPSV results using specific Fe-TauD potentials at the given mediator concentrations. However, no single ½ consistent with experimental observations across all the conditions tested here, giving strong support for intrinsic redox-linked reorganization in Fe-TauD, as follows.The largest hysteresis predicted for model[1] was 213 mV ( ½ TauD E = 0.0 mV), which is 85 mV smaller than that experimentally observed in 2OG-Fe-TauD and taurine-2OG-Fe-TauD and 128 mV smaller than that observed in Fe-TauD(Table S1). The magnitude of the hysteresis and apparent ½TauD E values in 2OG-Fe-TauD and taurine-2OG-Fe-TauD could be reproduced by model [2] using ½ A E = -130 mV and ½ A E  = 180 mV (Fig.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The application of a semi-empirical model of heterogeneous thin layer electrochemistry showed that both models can yield comparable NPSV results using specific Fe-TauD potentials at the given mediator concentrations. However, no single ½ consistent with experimental observations across all the conditions tested here, giving strong support for intrinsic redox-linked reorganization in Fe-TauD, as follows.The largest hysteresis predicted for model[1] was 213 mV ( ½ TauD E = 0.0 mV), which is 85 mV smaller than that experimentally observed in 2OG-Fe-TauD and taurine-2OG-Fe-TauD and 128 mV smaller than that observed in Fe-TauD(Table S1). The magnitude of the hysteresis and apparent ½TauD E values in 2OG-Fe-TauD and taurine-2OG-Fe-TauD could be reproduced by model [2] using ½ A E = -130 mV and ½ A E  = 180 mV (Fig.…”
mentioning
confidence: 62%
“…Calculated oxidation and reduction potentials of profiles generated using model[1]. Phases representing >50% of the observed oxidation or reduction are bolded.…”
mentioning
confidence: 99%
“…However, there were aspects of the unique gene sets worth noting. OlV7 generally showed enrichment of functions involved in gene expression, such as expansion of the Fe(II)/2‐oxoglutarate‐dependent oxygenase protein family, which encompasses diverse functions affecting multiple steps in transcriptional and translational processes, as well as biosynthesis and degradation of cellular metabolites (Herr and Hausinger, ). Several cyanophage genomes also encode multiple copies of 2OG‐Fe(II) oxygenase superfamily proteins, presumed to function in DNA repair (Weigele et al, ; Sullivan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In einer glücklichen Fügung für Ratcliffe beschäftigte sich eine andere Gruppe an der Universität Oxford um Christopher Schofield mit nicht-Häm Fe II -abhängigen Oxygenasen der Antibiotikabiosynthese und metabolischer Prozesse: [19] Diese Enzymklasse koppelt die Vier-Elektronen-Reduktion von molekularem Sauerstoff an die Oxidation sowohl des primären Substrats als auch die des Cosubstrats 2-Oxoglutarat (2OG). Vertreter dieser 2OG-abhängigen Dioxygenasen, die die Einführung oxidativer Modifikationen an Proteinen katalysieren, waren bereits bekannt, aufgrund von Arbeiten zur posttranslationalen Hydroxylierung von Lysin und Prolin im Kollagen oder auch Aspartyl-und Asparaginylhydroxylierung des epidermalen Wachstumsfaktors.…”
Section: Der Sauerstoffsensor Der Menschlichen Zellenunclassified